2007
DOI: 10.1080/14620316.2007.11512232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-storage heat treatment on fruit ripening and decay development in different apple cultivars

Abstract: Apple fruits of different cultivars were heat-treated at 38°C for 4 d immediately after harvest, then stored at 0°C for 6 weeks ('Gala') or 4 months ('Golden Delicious' and 'Red Fuji'). Upon removal from storage, fruits were kept for 7 d at 20°C as a shelf-life test. During storage and shelf-life, various ripeness parameters were measured. 'Golden Delicious' and 'Red Fuji' apples were artificially inoculated with Penicillium expansum or Botrytis cinerea before heat treatment, then stored at 20°C for 3 weeks, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…These findings are in agreement with previous reports of HT on apple fruit (Lurie and Klein 1990; Klein et al . 1998; Shao et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in agreement with previous reports of HT on apple fruit (Lurie and Klein 1990; Klein et al . 1998; Shao et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no heat damage could be found on the apples heat‐treated before CTS coating (HT + CTS) during the whole storage. After the HT at 38C for 4 days, the respiration rate declines to near or below the level of the nonheated control apples (Klein and Lurie 1990; Lurie and Klein 1990; Shao et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HT could decrease firmness loss and maintain a higher soluble solids/titratable acid ratio in apples after regular cold storage (Porritt & Lidster, ; Klein & Lurie, ; Lurie & Klein, ; Saftner et al ., , ). It has been shown to reduce ethylene production and control superficial scald in apple (Jemric et al ., ; Shao et al ., ), reduce ethylene production and inhibit peel spotting in banana (Ghasemnezhad et al ., ; Kamdee et al ., ), delay softening in strawberry (Martínez & Civello, ), improve tolerance to chilling injury in mandarins, tomato and pomegranate (Mirdehghan et al ., ; Ghasemnezhad et al ., ; Lu et al ., ), and HT was also effective in controlling against various postharvest diseases on grapefruit (Pavoncello et al ., ), pineapple (Wijeratnam et al ., ), cherry tomato (Zhao et al ., ), loquat (Liu et al ., ), strawberry (Jing et al ., ), peach and nectarine (Jemric et al ., ). However, the response to heat treatment may be cultivar specific (Shao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ismail et al, (2006) reported that chemical and physical characteristics of the fruits influenced their mechanical and rheological properties, which in turn can be indicators of firmness and ultimately of quality. Postharvest treatment offers a pesticide free method to kill or weaken plant pathogens, control insect infestations and maintain fruit storage quality (Barkai-Golan and Phillips, 1991;Shao et al, 2007). From the last few years, the use of various chemicals, waxing material and fungicide are becoming popular among growers in order to enhance the shelf life of fruits.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 1838-1850mentioning
confidence: 99%